Did trade liberalization with China influence US elections? - Che, Yi; Lu, Yi; Pierce, Justin R.; Schott, Peter K.; Tao, Zhigang (Journal of international economics, 2022)
We examine election voting and legislators’ roll-call votes in the United States over a twenty-five year period. Voters in areas more exposed to trade liberalization with China in 2000 subsequently shift their support toward Democrats, relative to the 1990s, though this boost for Democrats wanes after the rise of the Tea Party in 2010. House members’ votes in Congress rationalize these trends, with Democratic representatives disproportionately supporting protection during the early 2000s. Together, these results imply that voters in areas subject to higher import competition shifted votes toward the party more likely to restrict trade.